1921
DOI: 10.1007/bf02895308
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sklerose und Beruf

Abstract: Die neueren i~tiologischen Forschungen bei multipler Sklerose [Sie merli ng und Raee k ea~ B ulloe k153), K uh n und Stei ner l~ 154), Simons155), MarineseolaS), Kalberlah156), SiemerlingV2), Bfis c h e r 43), Speer 147)] haben die infektiSse Entstehung der Erkrankung sehr wahrscheinlich gemacht. Es erhebt sich mit der Annahme der infek-tiSsen Genese die Frage: Wie kommt das Virus in den mensehlichen KSrper hinein ?. Nach allgemeiner Anschauung ist die multiple Sklerose im Kindesalter sehr selten, am h~ufigste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1926
1926
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…At the beginning of the 20th century, however, the sex ratio was estimated to be equal or even reversed [5]. Some earlier data series [1,[6][7][8][9][10][11][12][13] that illustrate the evidence of pioneer scholars are depicted in Table 1. Counterevidence first arose from two epidemiological prevalence studies in the 1920s, one of them by Bing in Switzerland [1,6,14] and the other by Allison in North Wales [13].…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…At the beginning of the 20th century, however, the sex ratio was estimated to be equal or even reversed [5]. Some earlier data series [1,[6][7][8][9][10][11][12][13] that illustrate the evidence of pioneer scholars are depicted in Table 1. Counterevidence first arose from two epidemiological prevalence studies in the 1920s, one of them by Bing in Switzerland [1,6,14] and the other by Allison in North Wales [13].…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…About the same time in Germany, Dreyfuss (1921) suggested that in some way the disease was connected with wood-working and farming, and Koch (1929) put forward evidence that it was more common in rural than among urban dwellers. At a much earlier period Oppenheim (1896) had observed its occurrence among lead, copper and phosphorus workers, in engravers and lithographers and among those who had to do with aniline dyes.…”
Section: By R S Allison Vrd Frcp (Belfast)mentioning
confidence: 99%